P322 A MISLEADING SAM. (18th May 2022) - Armillotta, M; Sansonetti, A; Amicone, S; Stefanizzi, A; Impellizzeri, A; Bergamaschi, L; Paolisso, P; Foà, A; Rinaldi, A; Casella, G; Galiè, N; Pizzi, C
Abstract: A 66–year–old woman with a history of anxious–depressive syndrome and osteoporosis, without significant cardiological history, reported onset of cardiopalmus and dyspnoea for a few days due to moderate efforts, in conjunction with a period of strong emotional stress. Due to the persistence of these symptoms and the onset of epigastric pain, she underwent a cardiological examination which found low blood pressure values associated with the presence of a systolic murmur. The ECG showed diffuse changes in repolarization compatible with ischemia. Access to the emergency room (ER) was recommended. In ER, the first high–sensitivity troponin value was significantly high (1542 ng/L). Therefore, in the suspect of ACS, the patient was transferred to the cardiological intensive care unit. Echocardiogram showed akinesia of the mid–apical segments, hypercontractility of the bases (EF 35%) and a SAM (systolic anterior motion) with a dynamic outflow tract pressure gradient of 80 mmHg which resulted in severe mitral regurgitation. During the first days of hospitalization, persistent hypotension was observed requiring intravenous infusion of fluids to maintain systolic blood pressure values between 90–100 mmHg. Coronary angiography showed only severe ostial stenosis of a branch of the first diagonal branch. At the same time, ventriculography was performed which showed basal hypercontractility with muscle salience at the base and systolic obliteration of the outflow tract with a small apical aneurysm. 5 days after admission, another echocardiogram showed the almost complete normalization of the global systolic function (EF 68%) with apical hypokinesia and hypercontractility of the basal segments. However, the SAM persisted with a dynamic outflow tract pressure gradient of 140 mmHg with the presence of multiple and dislocated papillaries, accessory tendon cords and insertion of muscle tendon at the level of the septum. To complete the diagnosis, cardiac MRI was performed which documented a diffuse increase in T2 relaxation times more evident in the apical area, absence of LGE areas and normalization of contractility of the left ventricle with disappearance of the SAM. These findings, together with the absence of significant hypertrophy and the complete regression of the ECGgraphic changes, allowed us to exclude the presence of an unrecognized hypertrophic cardiomyopathy and to diagnose Takotsubo syndrome.